Investigations into Recycling Zinc from Used Metal Oxide Varistors via pH Selective Leaching: Characterization, Leaching, and Residue Analysis - Toni Gutknecht; Anna Gustafsson; Christer Forsgren; Christian Ekberg; Britt-Marie Steenari (The Scientific World Journal)
Metal oxide varistors (MOVs) are a type of resistor with significantly nonlinear current-voltage characteristics commonly used in power lines to protect against overvoltages. If a proper recycling plan is developed MOVs can be an excellent source of secondary zinc because they contain over 90 weight percent zinc oxide. The oxides of antimony, bismuth, and to a lesser degree cobalt, manganese, and nickel are also present in varistors. Characterization of the MOV showed that cobalt, nickel, and manganese were not present in the varistor material at concentrations greater than one weight percent. This investigation determined whether a pH selective dissolution (leaching) process can be utilized as a starting point for hydrometallurgical recycling of the zinc in MOVs. This investigation showed it was possible to selectively leach zinc from the MOV without coleaching of bismuth and antimony by selecting a suitable pH, mainly higher than 3 for acids investigated. It was not possible to leach zinc without coleaching of manganese, cobalt, and nickel. It can be concluded from results obtained with the acids used, acetic, hydrochloric, nitric, and sulfuric, that sulfate leaching produced the most desirable results with respect to zinc leaching and it is also used extensively in industrial zinc production.